Macrophages, a cellular toolbox used by tumors to promote progression and metastasis - Pollard, Jeffrey (Henry Stewart Talks, 2009)
Tumor microenvironment, Macrophages promote tumor progression and metastasis, Macrophage densities correlate with poor prognosis in many human cancers, Macrophages regulate tumor cell migration and intravasation, Macrophages regulate the angiogenic switch at the malignant transition, Macrophage and tumor cells move using a paracrine mechanism involving CSF-1 and EGF, Macrophages synthesize VEGF to regulate angiogenesis